Evaluation of atherosclerosis risk by measurement of intima media thickness and pulse wave velocity in lichen planus patients; A prospective case-control study - Koç, Saliha; Küçük, Murathan; Tosun, Veysel; Öncel, Can Ramazan; Alpsoy, Erkan; Yılmaz, Ertan (Journal of Surgery and Medicine, 2017)
Aim: Lichen planus (LP) is one of the chronic inflammatory diseases. Chronic inflammation may play an important role in the development of subclinical atherosclerosis. In this study, we aimed to investigate the relationship between LP and atherosclerosis by using carotid intima media thickness (CIMT) and pulse wave velocity (PWV) measurements. Methods: A controlled study is designed, two groups were formed as LP and control group. Forty LP patients (32 female and 8 male; mean age 44.6±1.2 years) and 40 healthy (control) individuals (32 female and 8 male; mean age 41.2±0.9 years) enrolled in the study. Individuals with atherosclerotic risk factors were excluded from the study for both groups. Demographic and biochemical data were recorded for both groups. CIMT and PWV measurements were compared between healthy and LP patients. Results: Maximum and average CIMT values in LP patients were significantly higher than the control group (Right maximum CIMT; 0.77±0.01 vs. 0.74±0.01, p=0.01, Left maximum CIMT; 0.80±0.01 vs. 0.76±0.01, p=0.011, Right average CIMT; 0.65±0.01 vs. 0.63±0.01, p=0.039, Left average CIMT; 0.68±0.01 vs. 0.64±0.01, p=0.005, respectively). No statistically significant difference was found between LP patients and control group for PWV (6.34±0.30 vs. 6.79±0.70 respectively, p=0.131). Conclusions: Our study demonstrated that CIMT was increased in patients with LP who had no clinical evidence of heart disease. LP patients were under an increased risk of subclinical atherosclerotic vascular dysfunction and structural changes.